After the rain : gentle reminders for healing, courage, and self-love - Elle, Alexandra (Chronicle Books, 2020)
"In this soulful companion, celebrated self-care storyteller Alexandra Elle delivers fifteen lessons on navigating life's twists and turns with a clear mind, courageous spirit, and open heart"--